The Makers And The Takers- An Empirical Study on Management Education at Business Schools in Hyderabad - MURTHY, Dr. K V RAMANA; TALLURI, Dr. VANISREE (The journal of contemporary issues in business and government, 2021)
Indian Economy is progressing at a considerable pace. There are enough number of opportunities in Information Technology, Pharma, BPOs, KPOs, manufacturing and other sectors. It is a fact that the growth of these sectors is dependent on the supply of amply qualified and skilled managers. Many Business Schools and Management Educational Institutions are working in this direction The present study aims to know the initiatives of business schools at Hyderabad in general and ICBM-SBE in specific. The objectives of the study are: to identify some of the dimensions of management education, to know the reasons for low outcomes in some of the conventional MBA colleges and to know the perceptions of the students about the quality of management education programmes at ICBM- SBE. Both primary and secondary data have been used for analysis. The sample size is 525. Purposive sampling is used. Statistical tools such as chi-square test, geometric mean, factor analysis and means scores on three point and five point rating are used for analysis. Two brand equity models, Viz., Brandz Model and Keller’s Model have been adapted. The concluding part of the study states that the quality of management education revolves around three Is viz., Initiatives, Internal Processes and Insights. ICBM – School of Business Excellence which is at the top of the pyramid in both the brand equity models, is well appreciated for the commitment, intertwining information technology with transformation technology and above all for its insight. The makers (The management and staff of ICBM) are quite successful in convincing and drawing the attention of the takers (About 150 recruiters).